A Rare Condition: The Ureteritis Cystica A Report of Two Cases and Review of the Literature - Kilic Semih Yasar Sargin, Suleyman; Gunes, Ali; Ipek, Deniz; Baydinc, Can; Altinok, M.Tayfun (Annals of Medical Research, 2021)
None